Touch may reduce cognitive load during assisted typing by individuals with developmental disabilities - Nicoli, Giovanni; Pavon, Giulia; Grayson, Andrew; Emerson, Anne; Mitra, Suvobrata (Frontiers in Integrative Neuroscience, 2023)
Many techniques have attempted to provide physical support to ease the execution of a typing task by individuals with developmental disabilities (DD). These techniques have been controversial due to concerns that the support provider’s touch can influence the typed content. The most common interpretation of assisted typing as an ideomotor phenomenon has been qualified recently by studies showing that users with DD make identifiable contributions to the process. This paper suggests a neurophysiological pathway by which touch could lower the cognitive load of seated typing by people with DD. The required sensorimotor processes (stabilizing posture and planning and executing manual reaching movements) and cognitive operations (generating and transcribing linguistic material) place concurrent demands on cognitive resources, particularly executive function (EF). A range of developmental disabilities are characterized by deficits in sensorimotor and EF capacity. As light touch has been shown to facilitate postural coordination, it is proposed that a facilitator’s touch could assist the seated typist with sensorimotor and EF deficits by reducing their sensorimotor workload and thereby freeing up shared cognitive resources for the linguistic elements of the task. This is the first theoretical framework for understanding how a facilitator’s touch may assist individuals with DD to contribute linguistic content during touch-assisted typing.